MHC class II B diversity in blue tits: a preliminary study. Issue 7 (21st May 2013) - de Aguilar, Juan Rivero‐; Schut, Elske; Merino, Santiago; Martínez, Javier; Komdeur, Jan; Westerdahl, Helena
Abstract: In this study, we partly characterize major histocompatibility complex (MHC) class II B in the blue tit ( Cyanistes caeruleus ). A total of 22 individuals from three different European locations: Spain, The Netherlands, and Sweden were screened for MHC allelic diversity. The MHC genes were investigated using both PCR‐based methods and unamplified genomic DNA with restriction fragment length polymorphism (RFLP) and southern blots. A total of 13 different exon 2 sequences were obtained independently from DNA and/or RNA, thus confirming gene transcription and likely functionality of the genes. Nine out of 13 alleles were found in more than one country, and two alleles appeared in all countries. Positive selection was detected in the region coding for the peptide binding region (PBR). A maximum of three alleles per individual was detected by sequencing and the RFLP pattern consisted of 4–7 fragments, indicating a minimum number of 2–4 loci per individual. A phylogenetic analysis, demonstrated that the blue tit sequences are divergent compared to sequences from other passerines resembling a different MHC lineage than those possessed by most passerines studied to date. Abstract : In this study, we partly characterize major histocompatibility complex (MHC) class II B in the blue tit (Cyanistes caeruleus). A total of 22 individuals from three different European locations: Spain, The Netherlands, and Sweden were screened for MHC allelic diversity.